A Study On The Potential Of Inclusion Of Environmental Management Elements In Contract Documents Of Construction Projects In Malaysia - Abdul Rahim, Asyirah (2017)
Strategic environmental management in the Malaysian construction industry is very much needed to translate the mission of sustainable development for effective environmental best practices at construction site. Inclusion of environmental management elements in contract documents of construction projects was chosen as the sustainable development strategy at project level. The study aimed to determine the strategic position of environmental management in construction projects and to recommend key drivers for changing the strategy into action.